SleepNow – A combined cognitive behavioral therapy for insomnia and physical exercise intervention in men with metastatic prostate cancer: results from a feasibility randomized controlled trial - Beverley Lim Høeg; Katrine Bjerre Løppenthin; Josée Savard; Christoffer Johansen; Jesper Frank Christensen; Mads Nordahl Svendsen; Niels Holländer; Pernille Envold Bidstrup (Acta Oncologica)
focused on patients living with metastatic cancer. We examined the feasibility of the SleepNow intervention combining cognitive behavioral therapy for insomnia (CBT-I) with physical exercise in men with metastatic prostate cancer (mPCa).